2014
DOI: 10.35188/unu-wider/2014/742-4
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of industry in Uganda

Abstract: Typescript prepared by Lisa Winkler at UNU-WIDER. UNU-WIDER gratefully acknowledges the financial contributions to the research programme from the governments of Denmark, Finland, Sweden, and the United Kingdom.The World Institute for Development Economics Research (WIDER) was established by the United Nations University (UNU) as its first research and training centre and started work in Helsinki, Finland in 1985. The Institute undertakes applied research and policy analysis on structural changes affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Uganda's manufacturing sector is growing, but it currently accounts for just 18.4 per cent of GDPcompared to 48 per cent for services and 26.2 per cent for agriculture (World Bank Report, 2015). Manufacturing is heavily reliant on imported materials and is faced with challenges like high interest rates, poor transportation infrastructure, inadequate skills and power shortages (Obwona et al 2014). Further, unethical behaviour in commercial transactions is common.…”
Section: Context and Case Selectionmentioning
confidence: 99%
“…Uganda's manufacturing sector is growing, but it currently accounts for just 18.4 per cent of GDPcompared to 48 per cent for services and 26.2 per cent for agriculture (World Bank Report, 2015). Manufacturing is heavily reliant on imported materials and is faced with challenges like high interest rates, poor transportation infrastructure, inadequate skills and power shortages (Obwona et al 2014). Further, unethical behaviour in commercial transactions is common.…”
Section: Context and Case Selectionmentioning
confidence: 99%
“…In the 1950s and 1960s, gold mining was identified as the main source of economic growth in the country, generating about 30 per cent of Uganda's export earnings. 36 The economic and political instability that affected the country in the 1970s resulted in the shutting down of many industrial mines, thus opening wide the doors to artisanal and small-scale gold-mining activities. 37 Muhumuza reports that Uganda has experienced an explosive rush in gold mining, with 10,000 artisanal gold miners in the Mubende district, and with 15,000 to 80,000 miners at the Rupa gold mine in Karamoja.…”
Section: Child Labour: a Conceptual Frameworkmentioning
confidence: 99%
“…While 10 years ago the list might have been dismissed by some as a PR stunt (or trial balloon), the professional skills it identified were subsequently validated by the Government's policy stances as well as by the requirements of the oil companies, i.e. as reflected by their employment, national content, and industrial policies (Obwana et al 2016). Moreover, Makerere University, with support from the China University of Petroleum, has set up an Institute of Geo-Sciences and Petroleum, and offers a Bachelor of Science in Petroleum.…”
Section: Technical Elitesmentioning
confidence: 99%